Comparative Study of Thigh Muscles and Bones Conformation and Some Carcass Traits of Local vs. Imported Turkey Strain - Taha, N.T.; Farran, M.T. (International Journal of Poultry Science, 2009)
Four males and four females of each of imported BUT-9 and local strain of turkey were slaughtered at marketing age, to study live body weight, som carcass traits, in addition to drumstick’s bones at Tibia region “Nazarian bones2” which radiography and chemically analyzed for fat-free bone parameters. The results indicated that BUT-9 revealed higher (p